2003
DOI: 10.1038/sj.ejcn.1601812
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient adequacy and Mediterranean Diet in Spanish school children and adolescents

Abstract: Objective: To evaluate dietary habits and nutritional status of Spanish school children and adolescents, and their relationship with the Mediterranean Diet. Design: Cross-sectional study by face-to-face interview. Setting: Free living children and adolescents of all Spanish regions. Subjects: A random sample of 3166 people aged 6-24 y. Methods: Home interviews conducted by a team of 43 dietitians included 24-h recalls (a second 24-h recall in 25% of the sample) and a short frequency questionnaire to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
102
2
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 19 publications
6
102
2
9
Order By: Relevance
“…Consequently, some questions could arise regarding the effectiveness of the MD in pregnancy in relation to the increased maternal nutritional needs during this period. First, several studies have demonstrated the high nutritional quality of the MD characterised by better dietary fat quality and an increased quantity of antioxidants (43,44) . Because alcohol consumption is prohibited in pregnancy, and during this period there is increased need for Ca intake, we did not include in the index alcohol consumption and we presumed dairy compounds to be protective and not detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, some questions could arise regarding the effectiveness of the MD in pregnancy in relation to the increased maternal nutritional needs during this period. First, several studies have demonstrated the high nutritional quality of the MD characterised by better dietary fat quality and an increased quantity of antioxidants (43,44) . Because alcohol consumption is prohibited in pregnancy, and during this period there is increased need for Ca intake, we did not include in the index alcohol consumption and we presumed dairy compounds to be protective and not detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…BMI groups were calculated according to the cut-off points for adolescents' BMI defined by the International Obesity Taskforce (IOTF) (31) . Three categories were used to define adolescents' MDP adherence according to the KIDMED questionnaire (28)(29)(30) : (i) #3 points was defined as very poor adherence; (ii) 4-7 points was defined as medium adherence; and (iii) $8 points was defined as high adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Four questionnaires were given to the participants for completion in the classroom: (i) a questionnaire on personal characteristics, socio-economic status (SES) and parents' education level; (ii) a twenty-item questionnaire based on the principles of the Mediterranean diet pyramid (26) for the assessment of adolescents' perceived and actual knowledge about the MDP and its health outcomes; (iii) an FFQ for the assessment of their past-week dietary habits (27) ; and (iv) a brief (sixteen-item) questionnaire (KIDMED) for assessment of their adherence to the MDP that has been successfully used among children and adolescents in Spain (28)(29)(30) .…”
Section: Questionnairesmentioning
confidence: 99%
“…Calcium, iron and vitamin D deficiencies were found among underprivileged populations in several European countries (Serra-Majem et al, 2003). Adequate nutrition contributes to the well being of children and their potential learning ability (Walker et al, 2000).…”
Section: Discussionmentioning
confidence: 99%